Coping Strategies of Educating Students with Special Needs in Gombe State - Umar, M. Fatima (Kashere Journal of Education, 2022)
Students with special needs are facing a number of problems which they are finding difficult to cope with. In the light of this, this study examined the coping strategies of students with special needs in Gombe State. The demographic variables of gender and type of disability were tested on the respondents’ view. The research design adopted for this study was a descriptive survey. A multi-stage sampling technique was employed to select 257 participants in the study. However, 216 questionnaire forms were valid for data analysis. The instrument used was entitled “Coping Strategies of Students with Special Needs Questionnaire (CSSSNQ)”. Test re-test method was used to establish the reliability of the instrument as co-efficient of 0.73 was obtained. Mean and rank order was used to answer the research questions raised, while t-test and Analysis of Variance (ANOVA) were employed to test the hypotheses formulated at 0.05 level of significance. The findings revealed that some of the coping strategies employed by these students are working hard to solve their own problems individually, accepting special needs condition as God wishes and avoiding thinking about special needs situation. Based on the findings of this study, it is recommended that parents of children with special needs should provide for their personal and educational needs so that they can be able to benefit from teaching/learning process; the society should give strong financial, emotional and medical supports to students with special needs to enable them to adjust effectively to school environment; the school counsellors should, on regular basis, help students with special needs with emotional support and anxiety alleviation techniques so that they can become less apprehensive about their future and be able to achieve success in their educational endeavors.